Athabasca River Basin Research Institute Repository: Enhancing open access, education and research - Carter, Lisa; Tin, Tony (2012)
The Athabasca River Basin Research Institute (ARBRI) supports interdisciplinary research and knowledge transfer of the Athabasca River Basin, an area of more than 159,000 km2 that is distinct by its watersheds, lands, resources and communities. Recognizing that information related to the Athabasca River Basin is dispersed and in many different forms, and is often difficult to locate, a comprehensive online repository collecting as much information on the Athabasca River Basin has been developed. At the heart of the ARBRI is the commitment to collect materials and resources related specifically to the Athabasca River Basin that can be freely accessible to researchers, government, industry stakeholders, and community members, both locally and globally. Using advances in online technologies, a comprehensive searchable and interactive digitized repository is in development, using a number of platforms, such as research and technical reports and manuscripts, maps, videos, and audio records. This presentation will describe some of the advances in the development of the Athabasca River Basin Research Institute (ARBRI) repository that enables open and free access to materials.